2018
DOI: 10.1139/cjfr-2018-0027
|View full text |Cite
|
Sign up to set email alerts
|

Climate-sensitive radial increment model of Norway spruce in Tyrol based on a distributed lag model with penalized splines for year-ring time series

Abstract: A novel methodological framework is presented for climate-sensitive modeling of annual radial stem increment using year-ring width time series. The approach is based on a generalized additive model with penalized regression splines together with a distributed time lag model taking into account smooth nonlinear effects of a series of monthly temperature and precipitation values, as well as their interactions. Climate effects are also assumed to vary smoothly with time lag. The model framework enables both the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Our study demonstrated highly diverse subalpine tree growth responses to interannual climate variable fluctuations. This finding adds to a growing body of tree-ring research providing novel insights about the complexity of tree growth responses to climate variability (Girardin et al 2016, Buechling et al 2017, D'Orangeville et al 2018, Housset et al 2018, Klesse et al 2018, Marchand et al 2018, Millar et al 2018, Nothdurft and Vospernik 2018, Babst et al 2019, Büntgen et al 2019, Cailleret et al 2019, Correa-Díaz et al 2019, Hararuk et al 2019, Sáenz-Romero et al 2019. Interactions among ecological factors -tree size and life stage, species traits, and site conditions-and interannual fluctuations in temperature and precipitation, as well as decadal/multidecadal climate variability, can influence tree growth responses, sometimes in unexpected ways (Linderholm 2002, Millar et al 2018.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Our study demonstrated highly diverse subalpine tree growth responses to interannual climate variable fluctuations. This finding adds to a growing body of tree-ring research providing novel insights about the complexity of tree growth responses to climate variability (Girardin et al 2016, Buechling et al 2017, D'Orangeville et al 2018, Housset et al 2018, Klesse et al 2018, Marchand et al 2018, Millar et al 2018, Nothdurft and Vospernik 2018, Babst et al 2019, Büntgen et al 2019, Cailleret et al 2019, Correa-Díaz et al 2019, Hararuk et al 2019, Sáenz-Romero et al 2019. Interactions among ecological factors -tree size and life stage, species traits, and site conditions-and interannual fluctuations in temperature and precipitation, as well as decadal/multidecadal climate variability, can influence tree growth responses, sometimes in unexpected ways (Linderholm 2002, Millar et al 2018.…”
Section: Discussionmentioning
confidence: 72%
“…The relatively weak relationships we found between growth increment and PAS imply other factors play a more important role. Some studies reporting negative relationships between winter temperature and annual growth suggest the rapid consumption of stored carbohydrates needed for early reactivation of cambial growth may be a limiting factor (Sala et al 2012, Locosselli and Buckeridge 2017, Hartmann et al 2018, Nothdurft and Vospernik 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We chose the distance-dependent covariance function for an isotropic weakly stationary fractional Gaussian noise process (FNG, Baillie 1996). FNG's have been used to characterize 'long-term' memory processes (Johannesson et al 2007;Nothdurft and Vospernik 2018). Accordingly, the covariance between observations from two units or two points separated by a distance h is…”
Section: Ripley's Estimator Of Variancementioning
confidence: 99%